Analysis of the Cost of Footplate Foundation Work in the Construction of the Exit Gate and Cafeteria of Delta Surya Hospital, Sidoarjo District, Sidoarjo Regency - Djoni Irianto; Abdullah Ammar (Engineering And Technology Journal, 2024)
Cost is the main factor in a stage of a construction project that concerns the provision of funds that must be prepared by the project owner. Cost budgets have a crucial role in project implementation so they need to be taken into account to achieve efficiency and effectiveness in project implementation. In the cost analysis, a calculation of the unit price of wages, labor, materials and technical details of the work in detail has been determined for the planning of the total cost. The implementation of the construction of the Exit Gate and Cafeteria of Delta Surya Hospital is divided into several works, starting from preparatory work to finishing. Among these types of work, one of them is footplate foundation work which is further divided into sub-work or job description, namely excavation work, formwork work, ironing work, and casting work. Every work in a project requires cost planning or a Cost Budget Plan (RAB) with high precision to determine the amount of funds that must be provided in the work of a project to avoid losses for the parties involved. The discussion of this article will focus on cost analysis in the preparation of RAB which contains details of the cost of materials or materials, labor, equipment and overhead costs and a recapitulation of all costs for footplate foundation work by PT. Muliif Teknika Utama as a contractor from the description of the activity from the beginning to the end.